Developing a diagnosis calculator to estimate the probability of bacterial pneumonia - Jonathan D. Baghdadi; Ravi Tripathi; Lisa Pineles; Anthony D. Harris; Danica Palacio; Drew Charles; Kimberly C. Claeys; Emily Heil; Jackie Bork; Daniel J. Morgan (Cambridge University Press, 2023)
Misdiagnosis of bacterial pneumonia increases risk of exposure to inappropriate antibiotics and adverse events. We developed a diagnosis calculator (https://calculator.testingwisely.com) to inform clinical diagnosis of community-acquired bacterial pneumonia using objective indicators, including incidence of disease, risk factors, and sensitivity and specificity of diagnostic tests, that were identified through literature review.